Lupus Erythematosus Tumidus Mimicking Primary Cutaneous Marginal Zone B-cell Lymphoma - Megan H. Trager; Caroline Ram-Wolff; Jean-David Bouaziz; Maxime Battistella; Marie-Dominique; Jacqueline Rivet; Pauline Brice; Adèle de Masson; Larisa J. Geskin; Martine Bagot; Gabor Dobos (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)